2001
DOI: 10.1103/physrevb.63.134421
|View full text |Cite
|
Sign up to set email alerts
|

Electron-electron interactions in graphene sheets

Abstract: The effects of the electron-electron interactions in a graphene layer are investigated. It is shown that short-range couplings are irrelevant and scale towards zero at low energies, due to the vanishing of density of states at the Fermi level. Topological disorder enhances the density of states and can lead to instabilities. In the presence of sufficiently strong repulsive interactions, p-wave superconductivity can emerge.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
212
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(219 citation statements)
references
References 45 publications
7
212
0
Order By: Relevance
“…Our results demonstrate the two-dimensionality of the electron system in ideal graphite samples. Recent experimental and theoretical studies of graphite have renewed the interest in this system [1,2,3,4,5,6,7,8,9,10]. Experimental results show that, contrary to the common belief, the transport and magnetic properties of graphite cannot be accounted for by semiclassical models.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our results demonstrate the two-dimensionality of the electron system in ideal graphite samples. Recent experimental and theoretical studies of graphite have renewed the interest in this system [1,2,3,4,5,6,7,8,9,10]. Experimental results show that, contrary to the common belief, the transport and magnetic properties of graphite cannot be accounted for by semiclassical models.…”
Section: Introductionmentioning
confidence: 67%
“…Based on magnetization data [2] and the found 2D scaling similar to that in the MIT of Si-MOSFETs (metal-oxide-semiconductor field-effecttransitor) [11], Mo-Ge [12] and Bi-films [13], the MIT in graphite has been interpreted in terms of superconducting fluctuations [1,3]. It has been shown that the density of states at the Fermi level is enhanced through topological disorder, thus leading to the possible occurrence of localized ferromagnetism and superconductivity [7].…”
mentioning
confidence: 99%
“…The superconducting state coexists with the ferromagnetism of pure graphite, and a continuous crossover from superconducting to ferromagnetic-like behavior could be achieved by increasing the magnetic field or the temperature. The angular dependence of the magnetic moment m(α) provides evidence for an interaction between the ferromagnetic and the superconducting order parameters.An interplay between ferromagnetic (FM) and superconducting (SC) behavior of graphite and related systems has recently been observed [1,2] and theoretically analyzed [3,4]. In particular, it has been demonstrated that the SC of graphite-sulfur (C-S) composites occurring within some sort of "grains" or domains [5,2] is highly anisotropic and associated with the graphite planes [2].…”
mentioning
confidence: 99%
“…An interplay between ferromagnetic (FM) and superconducting (SC) behavior of graphite and related systems has recently been observed [1,2] and theoretically analyzed [3,4]. In particular, it has been demonstrated that the SC of graphite-sulfur (C-S) composites occurring within some sort of "grains" or domains [5,2] is highly anisotropic and associated with the graphite planes [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation